2014
DOI: 10.1189/jlb.0114051
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Recovery from chemotherapy depends on STAT1 for replenishment of B lymphopoiesis

Abstract: Discussion of how B cell immune function is affected after hematopoietic reconstitution in a situation of chemotherapy upon STAT1 deficiency, possibly impairing bone marrow transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, it may be hypothesized that decreased STAT-1 expression results in reduced tumor radiosensitivity via the ATM checkpoint. Similar studies have revealed that STAT-1-positive cancer may improve chemosensitivity of the tumor (10,13,14), whereas STAT-1 activation by IFN-α/β and antineoplastic drugs may exert a synergistic effect on the induction of apoptosis (5). In addition, the functions of the topoisomerase I inhibitor irinotecan on squamous cell carcinoma, and those of the antimetabolite raltitrexed, appear to depend on the expression of STAT-1 (15), thus suggesting that similar mechanisms may exist in glioma.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, it may be hypothesized that decreased STAT-1 expression results in reduced tumor radiosensitivity via the ATM checkpoint. Similar studies have revealed that STAT-1-positive cancer may improve chemosensitivity of the tumor (10,13,14), whereas STAT-1 activation by IFN-α/β and antineoplastic drugs may exert a synergistic effect on the induction of apoptosis (5). In addition, the functions of the topoisomerase I inhibitor irinotecan on squamous cell carcinoma, and those of the antimetabolite raltitrexed, appear to depend on the expression of STAT-1 (15), thus suggesting that similar mechanisms may exist in glioma.…”
Section: Discussionmentioning
confidence: 68%
“…STAT-1 has been identified as a tumor-inhibiting factor, and reduced STAT-1 expression is associated with the occurrence and progression of malignant tumors (4). In addition, it has been demonstrated that the activation of STAT-1 expression in tumor cells by exogenous or endogenous stimuli can improve the sensitivity of these cells to chemotherapy (5). The p53 gene has been classified as a tumor suppressor gene that can effectively inhibit cellular growth and response to stress in various cell types by inducing temporary or permanent suppression of proliferation, or by activating cell death processes.…”
Section: Introductionmentioning
confidence: 99%